Structure sensitive photocatalytic reduction of nitroarenes over TiO 2 - Swapna Challagulla (Nature Portfolio, 2017)
Abstract It is a subject of exploration whether the phase pure anatase or rutile TiO2 or the band alignment due to the heterojunctions in the two polymorphs of TiO2 plays the determining role in efficacy of a photocatalytic reaction. In this work, the phase pure anatase and rutile TiO2 have been explored for photocatalytic nitroarenes reduction to understand the role of surface structures and band alignment towards the reduction mechanism. The conduction band of synthesized anatase TiO2 has been found to be more populated with electrons of higher energy than that of synthesized rutile. This has given the anatase an edge towards photocatalytic reduction of nitroarenes over rutile TiO2. The other factors like adsorption of the reactants and the proton generation did not play any decisive role in catalytic efficacy.